2017
DOI: 10.3390/molecules22122045
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of G2/M Transition by Inhibition of WEE1 and PKMYT1 Kinases

Abstract: In the cell cycle, there are two checkpoint arrests that allow cells to repair damaged DNA in order to maintain genomic integrity. Many cancer cells have defective G1 checkpoint mechanisms, thus depending on the G2 checkpoint far more than normal cells. G2 checkpoint abrogation is therefore a promising concept to preferably damage cancerous cells over normal cells. The main factor influencing the decision to enter mitosis is a complex composed of Cdk1 and cyclin B. Cdk1/CycB is regulated by various feedback me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(79 citation statements)
references
References 91 publications
2
77
0
Order By: Relevance
“…After an extensive literature review of these 14 genes, we found that PKMYT1 is a highly promising gene that may be closely related to tumor radiosensitivity. This is because PKMYT1 is currently considered to be the target of G2 checkpoint elimination and mitotic catastrophe (Tse et al, 2009;Schmidt et al, 2017) as it can prevent cells from transitioning from G2 to mitosis phase by affecting the activity of Cdk1 and the nuclear shuttle of the Cdk1-CycB complex (Fattaey and Booher, 1997;Wells et al, 1999;Passer et al, 2003). Additionally, the abrogation of the G2 checkpoint effectively reduced radiationinduced cell cycle arrest and increased tumor radiosensitivity (Leijen et al, 2010;De Witt et al, 2011;Qin et al, 2014;Busch et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After an extensive literature review of these 14 genes, we found that PKMYT1 is a highly promising gene that may be closely related to tumor radiosensitivity. This is because PKMYT1 is currently considered to be the target of G2 checkpoint elimination and mitotic catastrophe (Tse et al, 2009;Schmidt et al, 2017) as it can prevent cells from transitioning from G2 to mitosis phase by affecting the activity of Cdk1 and the nuclear shuttle of the Cdk1-CycB complex (Fattaey and Booher, 1997;Wells et al, 1999;Passer et al, 2003). Additionally, the abrogation of the G2 checkpoint effectively reduced radiationinduced cell cycle arrest and increased tumor radiosensitivity (Leijen et al, 2010;De Witt et al, 2011;Qin et al, 2014;Busch et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…reduced radiation-induced cell cycle arrest and increased tumor radiosensitivity (Leijen et al, 2010;De Witt et al, 2011;Qin et al, 2014;Busch et al, 2017). Additionally, PKMYT1 is currently considered to be the target of G2 checkpoint elimination and mitotic catastrophe (Tse et al, 2009;Schmidt et al, 2017) because PKMYT1 can prevent cells from transitioning from G2 to mitosis phase in two ways. One is inhibiting Cdk1 activity via phosphorylating Cdk1 at Thr14 and Tyr15, and the other is preventing the Cdk1-CycB complex from entering the nucleus by binding to the Cdk1-CycB complex and sequestering it in the cytoplasm (Fattaey and Booher, 1997;Wells et al, 1999;Passer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The kinase WEE1 is a plausible candidate for such an upregulation. WEE1 inactivates the cyclin B1/CDK1 complex both at the entry into mitosis [61] and at the metaphase-to-anaphase transition [62]. WEE1 expression was increased by 30% in Kv10.1-deficient cells (0.16 ± 0.01 a.u.)…”
Section: Kv101 Downregulation Leads To Activation Of Spindle Assemblmentioning
confidence: 99%
“…Supplementary Data S3 lists individual affected genes in this pathway. PrP(GPI) Drosophila were characterised by up-regulation of genes encoding the Cdk1-cyclin B complex, which serves to trigger mitosis in eukaryotic cells [39] and Wee1, a tyrosine kinase Cdk1 regulator [40]. In addition, there was up-regulation of expression of lok, a serine/threonine-protein kinase required for checkpointmediated cell cycle arrest, activation of DNA repair and apoptosis in response to the presence of DNA doublestrand breaks [41]; Aura, a mitotic serine/threonine kinase that contributes to the regulation of cell cycle progression [42]; TOP2, a topoisomerase II that controls topological states of DNA by transient breakage and subsequent re-joining of DNA strands [43]; polo, a Serine/threonine-protein kinase that functions throughout cell cycle M phase [44]; and grp, a Serine/threonine-protein kinase required for checkpoint-mediated cell cycle arrest and activation of DNA repair in response to the presence of DNA damage or un-replicated DNA [45].…”
Section: Eif2 Signalling and Cell Cycle Activity Are Perturbed In Primentioning
confidence: 99%